Microbial redox coenzyme engineering and applications in biosynthesis. Issue 4 (April 2022) - Yang, Haiqian; Jia, Xiaojing; Han, Yejun
Abstract : Many biosynthetic processes, either in vivo or in vitro, involve redox reactions catalyzed by oxidoreductases – which depend on coenzymes as electron carriers. Redox balance is regulated mainly by coenzymes NAD(P) + and NAD(P)H and is essential for biosynthesis. New techniques for the regulation and regeneration of coenzymes have recently advanced our understanding of, and demonstrated promising applications in, synthetic biology.